Examining the factors affecting saving in Malaysia / Nur Hanian Athirah Mohd Zali - Mohd Zali, Nur Hanian Athirah (Faculty of Business Management, 2018)
Savings is remaining income left after paying consumptions. It is play an important role as a catalyst for development and growth of economic in a country. Highs saving in a country will drive the investment rate that can stimulate towards economic growth. The main purpose of this paper is to analyze the factors that affecting saving in Malaysia over the period from year 1987 to 2016. The dependent variable of this research is household saving rate and this research using five (5) independent variables which are interest rate (IR), population growth (POP), gross national income per capita (GND, inflation rate (INF), and unemployment rate (UNE). These independent variables used to see whether there is significant or insignificant relationship with household saving rate. The data collected from Datastream was chosen for this study with the time period about 30 years which from 1987 to 2016 based on annually basis. Furthermore, the data that had been used in this research is quantitative secondary data and the data structure is time series data. This study found that, interest rate, population growth, inflation rate and unemployment rate are the most significant factors affecting saving in Malaysia.